Activated carbon-coated iron oxide magnetic nanocomposite (IONPs@CtAC) loaded with morin hydrate for drug-delivery applications - Doğan, Yusuf; Öziç, Cem; Ertaş, Erdal; Baran, Ayşe; Rosic, Gvozden; Selakovic, Dragica; Eftekhari, Aziz (Frontiers in Chemistry, 2024)
Cancer is a major disease that affects millions of people around the world every year. This disease affects individuals of all ages, races and backgrounds. Since drugs used to treat cancer cannot distinguish between cancerous and healthy cells, they cause systemic toxicity along with serious side effects. Recently, controlled drug release systems have been developed to reduce the side effects caused by anti-cancer drugs used for treatment. Morin is an anticancer drug with a flavonol structure that has been extensively researched for its antioxidant, anti-inflammatory, antitumoral and antibacterial properties, especially found in Chinese herbs and fruits, as well as its multiple positive effects on different diseases. In this study, biocompatible activated carbon obtained using the fruits of the Celtis tournefortii plant was coated on the surface of iron oxide magnetic nanoparticles and a nanocomposite with magnetic properties was synthesized. Characterization of the synthesized activated carbon-coated iron oxide magnetic nanocomposite was confirmed by Fourier Transform Infrared, Scanning Electron Microscopy, Energy Dispersive Xray Spectrometry, X-Ray Diffraction, dynamic light scattering , Zeta Potential and vibrating sample magnetometer. The cytotoxic effects of the drug-loaded magnetic nanocomposite were examined in HT-29 (Colorectal), T98-G (Gliablastoma) cancer cell lines and Human Umbilical Vein Endothelial Cells (HUVEC) healthy cell line. The Morin loading and release behavior of activated carbon-coated iron oxide magnetic nanocomposite was studied, and the results showed that up to 60% of the adsorbed morin was released within 4 hours. In summary, activated carbon-coated iron oxide magnetic nanocomposite carriers have shown promising results for the delivery of morin drug.